1999
DOI: 10.1006/dbio.1998.9108
|View full text |Cite
|
Sign up to set email alerts
|

FGF Is Required for Posterior Neural Patterning but Not for Neural Induction

Abstract: Fibroblast growth factor (FGF) has been implicated in a variety of developmental processes including posterior mesoderm and neural patterning. Previous work has led to contradictory roles for FGF in neural induction and anteroposterior neural patterning. Launay et al. (Development 122, 869-880, 1996) suggested a requirement for FGF in anterior neural induction. In contrast, Kroll and Amaya (Development 122, 3173-3183, 1996) and Bang et al. (Development 124, 2075-2085, 1997) proposed that FGF is not required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 57 publications
2
57
1
1
Order By: Relevance
“…Organizer-derived posteriorizing signals reach neuroectoderm during gastrulation to specify the anteroposterior axis (Nieuwkoop 1952;Doniach et al 1992;Holowacz and Sokol 1999). Besides Wnt signaling, this process requires additional pathways, such as BMP and FGF signaling.…”
Section: Cross Talk With Other Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizer-derived posteriorizing signals reach neuroectoderm during gastrulation to specify the anteroposterior axis (Nieuwkoop 1952;Doniach et al 1992;Holowacz and Sokol 1999). Besides Wnt signaling, this process requires additional pathways, such as BMP and FGF signaling.…”
Section: Cross Talk With Other Pathwaysmentioning
confidence: 99%
“…In contrast to the BMP pathway that is active in the ventral region of the blastula embryo, FGF signaling seems to be essential for dorsal posterior patterning (Amaya et al 1991;Cox and Hemmati-Brivanlou 1995;Lamb and Harland 1995;Holowacz and Sokol 1999;Schohl and Fagotto 2002;Kudoh et al 2004;Marchal et al 2009;Martin and Kimelman 2009). Many Wntinducible genes, including Cdx4, Xpo, Meis, and Marginal coil (Xmc), have been previously identified as FGF-responsive genes (Table 1) (Amaya et al 1993;Frazzetto et al 2002;Aamar and Frank 2004;Chung et al 2004;Keenan et al 2006).…”
Section: Cross Talk With Other Pathwaysmentioning
confidence: 99%
“…FGF does seem to be able to diffuse over several cell diameters (Christen and Slack, 1999), and it has been proposed to be a morphogen in early posterior patterning of the nervous system in Xenopus: embryonic FGF (eFGF) may act during gastrulation stages to induce expression of posterior Hox genes and posterior neural markers (Xu et al, 1997;Isaacs et al, 1998;Pownall et al, 1998;Holowacz and Sokol, 1999). However, more detailed analysis of FGF's potential morphogen activity is difficult because the rapid increase in anatomic complexity makes quantitation problematic.…”
Section: Morphogens In Vivo Part Ii: Fgfs and Bmpsmentioning
confidence: 99%
“…When the animal cap was treated with bFGF and BMP-antagonists, for example, noggin, the posterior neural tissues were differentiated in addition to the anterior tissues (Cox & Hemmati-Brivanlou 1995). An approach utilizing a dominant-negative form of the FGF receptor (XFD) showed that FGF signaling is essential for the posterior central nervous system (Holowacz & Sokol 1999). Although there has been accumulating evidence supporting the 'two step model', the existence of direct trunk neural inducers cannot be ruled out.…”
Section: It Has Been Widely Accepted Therefore That the Appearancmentioning
confidence: 99%